Pengaruh Penyesuaian Diri Terhadap Motivasi Belajar Mahasiswa Di Universitas Sebelas Maret Surakarta - Eka Wulan Astutik; Nafadhilla Refie Anjani; Dewi Khurun Aini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to investigate the effect of adjustment on student motivation at Sebelas Maret University. Quantitative research method with causality design was used to collect data from 40 students using accidental sampling method. Research instruments include self-adjustment scales and learning motivation scales that have been tested for validity and reliability. The results of a simple linear regression analysis showed that self-adjustment had a significant effect on student learning motivation (p-value = 0.000). The regression coefficient (Beta) indicates the magnitude of the change in learning motivation if self-adjustment increases by 1 point, while the coefficient of determination (R square) indicates that self-adjustment has an effect of 43.5% on learning motivation, with 56.5% influenced by other variables. The suggestion for future research is to consider the addition of other variables that influence learning motivation and extend this research to different educational contexts. These findings make an important contribution to the understanding of the factors that influence student motivation.